Student Discipline Towards Natural Science Learning at Secondary Schools in Muaro Jambi Regency - Astalini Astalini; Dwi Agus Kurniawan; Nugroho Kurniawan (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
Discipline towards science learning is defined as a habit that characterizes students in responding to nature and science object. This study aims to analyze the students' discipline toward science learning. The research using a quantitative approach, this study employed the use of the survey method. From  612 students, the Random Sampling technique was used to select the respondents. Thus, this study analyzed the data from 187 students of State Secondary Schools in Muaro Jambi Regency. The data obtained using questionnaires. The results of the study are based on the measurement of the indicators on the students' discipline in science learning. The findings show that in the first indicator, 69 % of students are categorized as very good. In the second indicator, discipline in joining science lessons, 35,8% of students are categorized as very good. In the third indicator, discipline in doing science tasks, 46% of students are categorized as good. In the fourth indicator, discipline in learning science at home, 47,1%  of students are categorized as fair. Based on these results, it can be concluded that the students’ discipline towards science learning is considered as positive.